Water quality assessment of reefs in the gulf of Cazones, southern Cuba, using microbiological and chemical indicators - Lugioyo, Gladys Margarita; González, Daymarlen; García, Ileana (Revista Ciencias Marinas y Costeras, 2020)
Coral reefs are some of the most threatened ecosystems due to the anthropogenic activity and climate change, from which the Caribbean Sea reefs have not escaped. The objective of this paper was to assess the quality of the waters adjacent to the reefs of the Gulf of Cazones, southern Cuba, using certain microbiological and chemical indicators. Two samplings were conducted in contrasting seasons, November 2015 (winter) and April 2017 (summer), where 13 water samples were taken (five on the ridges and eight on the front reefs). The most vulnerable reefs to environmental deterioration in both seasons, taking into consideration the microbiological and chemical indicators, were Southeast of Cayo Diego Pérez 2 (SE-Cy.DP2), Southeast of Cayo Diego Pérez 1 (SE-Cy.DP1), and South of Cazones Cove (S-EC) (Nirvana), since they had high concentrations of heterotrophic and sulphate-reducing bacteria, vibrio, and organic matter (COD). Based on the heterotrophic bacteria concentration, the trophic state of the waters ranged from mesotrophic to meso-eutrophic and the most deteriorated site resides at the West of the Cazones cove (O-EC), followed by the East of the Cazones cove (E- EC) and South of the Cazones cove (S-EC). This indicates that the waters surrounding these reefs are enriched with organic matter, both on the ridges and on the frontal reefs. The results obtained should serve as a warning because conditions exist for the gradual deterioration of these coral reefs.